Pengaruh Lingkungan Kerja terhadap Kinerja Pegawai di Daerah Pemekaran - Windi Junursa Darya Lesbaban; Suyadi Suyadi; Apandi Apandi (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of the work environment on employee performance at the Rawas Ulu Sub-district Office, North Musi Rawas Regency, as one of the agencies in the newly established region. The research method used was a quantitative method with a survey approach involving 30 employees as respondents. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed using the Partial Least Squares (PLS) technique. The results showed that the work environment had a positive and significant effect on employee performance, with a path coefficient of 0.968, a T-statistic of 101.881, and a P-value of 0.000. Motivation also had a positive and significant effect on employee performance, but it was unable to significantly mediate the effect of the work environment on performance. The research model had an R-Square value of 0.955, indicating that 95.5% of the variation in employee performance can be explained by the work environment and motivation. The conclusion of this study indicates that the work environment, both physical and non-physical aspects such as lighting, cleanliness, work relationships, communication, and a sense of safety, play a significant role in improving employee performance in government agencies in newly established regions.   Keywords: Newly Established Regions, Employee Performance, Work Environment, Partial Least Squares (PLS)